Transformasi Hukum Keluarga Islam dalam Perspektif Kesetaraan Gender Analisis Perbandingan Indonesia dan Maroko - Widia Usada; Sukiati Sukiati; Iwan Iwan (Lembaga Yasin AlSys, 2026)
The debate on gender relations in Islamic family law has intensified alongside increasing demands for the protection of women’s rights, legal modernization, and regulatory harmonization with the principles of justice and human rights. This condition makes family law reform an important issue in the legal systems of Muslim countries. This study aims to analyze gender equality policies in Islamic marriage law through a comparative study between Indonesia and Morocco. This study used a normative legal method with statutory and comparative approaches to the main regulations, namely Law Number 1 of 1974 concerning Marriage in Indonesia and the Mudawwanah in Morocco. The results showed that Indonesia and Morocco adopted different models of family law reform. Indonesia applies normative equality that is still influenced by patriarchal and hierarchical structures, whereas Morocco has developed the concept of husband–wife partnership through a more progressive reinterpretation of Islamic law. The conclusion of this study affirms that Islamic family law reform in both countries is equally directed toward strengthening gender equality, but Morocco, through the Mudawwanah, demonstrates more progressive changes in protecting the rights of women and children than Indonesia. The implications of this study indicate that Islamic family law reform needs to continue to be directed toward strengthening the principles of gender equality, the protection of women’s rights, and family justice without disregarding the fundamental values of Islamic law.